Quantifying mental arousal levels in daily living using additional heart rate. (March 2017) - Yang, Zhaofang; Jia, Wenyan; Liu, Guangyuan; Sun, Mingui
Highlights: Monitoring the mental arousal level is very helpful in mental health assessment. Additional heart rate is highly correlated with mental arousal level. A mathematical model is introduced to predict the additional heart rate. The model was verified on daily living episodes and show its effectiveness. Abstract: Monitoring the mental arousal level is an effective way of mental health assessment. Additional heart rate has been proved highly correlated with mental arousal level, which presents the changes of heart rate that caused by mental activities. A mathematical heart rate model is introduced to predict the heart rate in response to body movement, and then to calculate the additional heart rate and mental arousal level. The effectiveness of the proposed model was verified on the physical activity monitoring dataset, which contains ten kinds of daily activities of ten subjects. The proposed model was then applied to the data of one subject in daily living, and the mental activities are indicated clearly from the mental arousal level. The proposed heart rate model provides an efficient way to calculate the additional heart rate and then quantify the mental arousal level, which can serve as a powerful tool in the mental health assessment.